2016
DOI: 10.1103/physreve.93.043207
|View full text |Cite
|
Sign up to set email alerts
|

Energetic electron-bunch generation in a phase-locked longitudinal laser electric field

Abstract: Energetic electron acceleration processes in a plasma hollow tube irradiated by an ultraintense laser pulse are investigated. It is found that the longitudinal component of the laser field is much enhanced when a linear polarized Gaussian laser pulse propagates through the plasma tube. This longitudinal field is of π/2 phase shift relative to the transverse electric field and has a π phase interval between its upper and lower parts. The electrons in the plasma tube are first pulled out by the transverse electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 31 publications
0
16
0
Order By: Relevance
“…Previous studies 10,34,36 have shown that, in a hollow channel without significant ion expansion, the dominant contributor to electron acceleration is the electric field in the direction of the laser propagation, i.e. the longitudinal field E x .…”
Section: Phase Velocity In 2d and 3d Waveguidesmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies 10,34,36 have shown that, in a hollow channel without significant ion expansion, the dominant contributor to electron acceleration is the electric field in the direction of the laser propagation, i.e. the longitudinal field E x .…”
Section: Phase Velocity In 2d and 3d Waveguidesmentioning
confidence: 99%
“…The interaction of high-power ultra-intense lasers and structured (both nanostructured [1][2][3][4][5][6][7] and microstructured [8][9][10][11][12][13][14][15][16][17][18] ) targets has been a topic of great interest for its capability of enhancing the laser energy conversion efficiency 1 , high-order harmonics generation 19,20 , charged particles (relativistic electrons and ions 3,4,18 ) acceleration and the production of X-ray 1,[21][22][23] to γ-ray 15,16,24 radiation. The produced charged particle and photon beams have a wide range of applications from medical ion therapy 25,26 , nuclear physics 27,28 to photon-photon pair production [29][30][31] .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Among these structured targets is the microplasma waveguide (MPW); not only does it suppress the transverse diffraction of the pump laser, but it also enhances the longitudinal acceleration field [21,22]. Such targets have already shown their potential in electron acceleration [23,24], x-ray generation [25,26], production of ion beams [27,28] and manipulation of relativistic laser pulses [29]. In our previous work, simulations show that high charge (∼10 nC), high energy (∼100 MeV) and well-collimated (10 • ) electron bunches can be produced and accelerated by the transverse magnetic modes [30].…”
Section: Introductionmentioning
confidence: 99%